Monoclonal Gammopathy of Renal Significance with Deposits of Peculiar Morphology and Injuries of Secondary Thrombotic Microangiopathy: A Case Report and Review of the Literature - José C. De La Flor; Marina Alonso; Edna Sandoval; Alexander Marschall; Miguel Rodeles (Case Reports in Nephrology)
We present the case of an 82-year-old woman diagnosed with monoclonal gammopathy of renal significance (MGRS) with the presence of different and peculiar kidney lesions, who began treatment with bortezomib and dexamethasone, presenting during her evolution a relapse. Although the bone marrow biopsy in this case showed plasma cells as pathologic clone and there was also a reduction after chemotherapeutic treatment, rituximab was proposed as a second line. We suspected that the relapse was possibly due to another precursor as B-cell or lymphoplasmacytic cell clone. We review the literature and suggest that the treatment for MGRS should be patient-tailored, preferably by consulting a multidisciplinary team. Future research is needed to better understand the disease course and establish the efficacy and safety of the therapeutic approach for the relapse of MGRS.